2008
DOI: 10.1158/1078-0432.ccr-07-2238
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Resistance: The Role of DNA Repair Pathways

Abstract: Although platinum chemotherapeutic agents such as carboplatin, cisplatin, and oxaliplatin are used to treat a broad range of malignant diseases, their efficacy in most cancers is limited by the development of resistance. There are multiple factors that contribute to platinum resistance but alterations of DNA repair processes have been known for some time to be important in mediating resistance. Recently acquired knowledge has provided insight into the molecular mechanisms of DNA repair pathways and their effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
548
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 667 publications
(560 citation statements)
references
References 42 publications
3
548
3
6
Order By: Relevance
“…And the level of stemness protein (OCT4), which is considered key genes for the production of murine and human induced pluripotent stem cell (Bao et al, 2006;Martin et al, 2008), was higher in MTCSCs than TT cells. Moreover, the tumorigenesis of MTCSCs can cause the tumor when planted in nude mice only 10 3 , as previous reported (Baumann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…And the level of stemness protein (OCT4), which is considered key genes for the production of murine and human induced pluripotent stem cell (Bao et al, 2006;Martin et al, 2008), was higher in MTCSCs than TT cells. Moreover, the tumorigenesis of MTCSCs can cause the tumor when planted in nude mice only 10 3 , as previous reported (Baumann et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There are strong evidence coming from preclinical and clinical trials, indicating that ERCC1 has an independent predictive value regarding prognosis, response to treatment, recurrence and overall survival (Olaussen et al, 2006;Martin et al, 2008;Ozkan et al, 2010;Li et al, 2011;2013a;2013b;Zhang et al, 2013). ERCC1 enzyme is found in all tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are strong evidence coming from preclinical and clinical trials, indicating that ERCC1 has an independent predictive value regarding prognosis, response to treatment, recurrence and overall survival (Olaussen et al, 2006;Ozkan et al, 2010;Betti et al, 2011; Zhang et al, 2012; Zhang et al, 2013; Li et al, 2013; Li XD et al, 2013; Mechanicsville 2013). Although there are studies on ERCC1 expression level and effects of chemotherapy on survival in MPM from several countries, this is a relatively new topic with conclusions covering small groups (Martin et al, 2008;Righi et al, 2010; Zimling et al, 2012). …”
mentioning
confidence: 99%
“…Previous studies have indicated that DNA repair systems participate in platinum-based chemotherapy resistance [9][10][11][12] . DNA inter-or intra-crosslinks caused by platinum chemotherapy can be removed by several DNA repair pathways, including base excision repair (BER), nucleotide excision repair (NER) and mismatch repair (MMR) [10] .…”
Section: Introductionmentioning
confidence: 99%
“…DNA inter-or intra-crosslinks caused by platinum chemotherapy can be removed by several DNA repair pathways, including base excision repair (BER), nucleotide excision repair (NER) and mismatch repair (MMR) [10] . Most DNA damage can be successfully repaired by the above error-free DNA repair pathways.…”
Section: Introductionmentioning
confidence: 99%